Molecular engineering of Y‐series acceptors for nonfullerene organic solar cells. Issue 5 (11th September 2022) - He, Qiao; Ufimkin, Petr; Aniés, Filip; Hu, Xiantao; Kafourou, Panagiota; Rimmele, Martina; Rapley, Charlotte L.; Ding, Bowen
Abstract: The power conversion efficiencies (PCEs) of single‐junction organic solar cells (OSCs) have surpassed 19%, owing to the emerging Y‐series nonfullerene acceptors (NFAs). Undoubtedly, the power and flexibility of chemical design has been a strong driver for this rapid efficiency improvement in the OSC field. Over the course of the past 3 years, a variety of modifications have been made to the structure of the Y6 acceptor, and a large number of Y‐series NFAs have been reported to further improve performance. Herein, we present our insights into the rationale behind the Y6 acceptor and discuss the design principles toward high‐performance Y‐series NFAs. It is clear that structural modifications through choice of heteroatom, soluble chains, π spacers, central cores, and end groups alter the material characteristics and properties, contributing to distinctive photovoltaic performance. Subsequently, we analyze various design strategies of Y‐series‐containing materials, including polymerized small‐molecule acceptors (PSMA), non‐fused‐ring acceptors (NFRA), and all‐fused‐ring acceptors (AFRA). This review is expected to be of value in providing effective molecular design strategies for high‐performance NFAs in future innovations. Abstract : Y‐series materials are currently most promising nonfullerene acceptors in organic solar cells. A detailed comparison of Y6 and ITIC has been performed. Chemical modification approaches to Y6 are summarized along with discussion about the relationship between structural property and device performance. The progress of Y‐series‐containing materials has also been studied, which can provide further guidance for molecular design.